ANALISIS JUMLAH KROMOSOM DAN ANATOMI STOMATA PADA BEBERAPA PLASMA NUTFAH PISANG (MUSA SP.) ASAL KALIMANTAN TIMUR - Fitri Damayanti (Bioscientiae, 2007)
East Kalimantan is an area rich in banana germ plasm. Conservation should be focused not only on varieties of high economic values, but on those of unknown economic value as well. Studies on genetic, morphological, anatomical, and agronomical characters of plants are required to avoid duplications of germ plasm collections. In the present study six banana germ plasm accessions - AK1M, AK2M, AK3M, AK4M, AK7P and AK8P - from East Kalimantan were examined. The objective was to reveal the ploidy based on chromosome numbers and to characterize the anatomy of the stomata. Chromosome analysis revealed different ploidies: diploid and triploid, with chromosome number 2n=22 for accessions AK1M, AK2M, AK3M, AK4B, and AK7P, and 2n=33 for accession AK8P. There was a correlation between the sizes of the epidermal cell and the stomata. Accession AK8P with triploidy had bigger epidermal cells and stomatas. The stomatas were located on the upper and lower surfaces of leaves with the exception of acccession AK4B whose stomata were located only on the lower surface. The highest stomatal density on the upper surface (3227.18 /mm2) was shown by accession AK3M with stomatal index value of 6.44%, while the highest value on the lower surface (17222.22/mm2) was found on accession AK4B with stomatal index of 15.35%.